Unsub : a novel - Gardiner, Meg (Dutton, 2017)
"A riveting psychological thriller inspired by the never-caught Zodiac Killer, about a young detective determined to apprehend the serial murderer who destroyed her family and terrorized a city twenty years earlier. Caitlin Hendrix has been a Narcotics detective for six months when the killer at the heart of all her childhood nightmares reemerges: the Prophet. An UNSUB--what the FBI calls an unknown subject--the Prophet terrorized the Bay Area in the 1990s and nearly destroyed her father, the lead investigator on the case. The Prophet's cryptic messages and mind games drove Detective Mack Hendrix to the brink of madness, and Mack's failure to solve the series of ritualized murders--eleven seemingly unconnected victims left with the ancient sign for Mercury etched into their flesh--was the final nail in the coffin for a once promising career. Twenty years later, two bodies are found bearing the haunting signature of the Prophet. Caitlin Hendrix has never escaped the shadow of her father's failure to protect their city. But now the ruthless madman is killing again and has set his sights on her, threatening to undermine the fragile barrier she rigidly maintains for her own protection, between relentless pursuit and dangerous obsession. Determined to decipher his twisted messages and stop the carnage, Caitlin ignores her father's warnings as she draws closer to the killer with each new gruesome murder. Is it a copycat, or can this really be the same Prophet who haunted her childhood? Will Caitlin avoid repeating her father's mistakes and redeem her family name, or will chasing the Prophet drag her and everyone she loves into the depths of the abyss?"--